A true story of the 70s, in Bilwi, Puerto Cabezas. Manuelito Ugarte Gómez grandson Don Manolo (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
The work dedicated to the famous Manuelito Ugarte Gómez is circumscribed in the studies of the “History of Life”, because it rescues the experiences and ways of life of a group of kids who had to live a period in that the elementary rights of life were denied to us by the most perverse system in the history of our country, I refer to the Somoza Military Dictatorship (1936-1979). Faced with so many limitations of their own from what anthropology collects as denied and silenced cultures appears the figure of a child, whose Father was a captain of the FAN (National Air Force), who above the ideology he could having his offspring, Manuelito chose to live, live and harmonize with the poorest kids of the City of Puerto Cabezas (Bilwi). It is my intention, that this Life Story can be read by this protagonist as a deep recognition of all the moral, social and economic support that we he was able to toast in the seventies. While we suffered the onslaught of Somocismo in parallel the greatest glory of our country was brewing, the Sandinista Popular Revolution in 1979, architect of our elementary rights until we become part of the Faculties Project Preparatory without a doubt it was the greatest monumental work in educational matters, because it could shelter the workers, peasants, combatants and ex- combatants who gave our lives before and during the revolutionary process.
Keywords: Subaltern cultures; identity and belonging to the imaginary